2016
DOI: 10.21037/jtd.2016.05.51
|View full text |Cite
|
Sign up to set email alerts
|

Primary lung tumors invading the chest wall

Abstract: Chest wall (CW) involvement occurs in approximately 5% of all primary lung neoplasms.According to the most recent TNM classification, lung tumors invading CW are classified as T3, and they represent approximately 45% of all T3 lung cancers. The most common clinical symptom at presentation is chest pain (>60%), which is highly specific of CW infiltration (>90%). Dyspnoea and hemoptysis are also described, especially in case of large lesions. A realistic chance to cure locally advanced tumors invading CW is a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
19
1
3
Order By: Relevance
“…Furthermore, regarding primary thoracic wall tumors, Bagheri et al (5) reported that the presence of distal metastasis significantly worsened prognosis, and any significant effect on survival was regardless of whether reconstruction was performed. According to previous studies, the 5-year survival rates are 21–61% in patients with lung cancer who present with thoracic wall invasion (1,9) and 73.9–88.5% in those with tumors arising from the soft tissues of the thoracic wall (10,19), results that are comparable to those of our study. However, in our study, neither the R factor nor the N factor caused statistically significant differences in prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, regarding primary thoracic wall tumors, Bagheri et al (5) reported that the presence of distal metastasis significantly worsened prognosis, and any significant effect on survival was regardless of whether reconstruction was performed. According to previous studies, the 5-year survival rates are 21–61% in patients with lung cancer who present with thoracic wall invasion (1,9) and 73.9–88.5% in those with tumors arising from the soft tissues of the thoracic wall (10,19), results that are comparable to those of our study. However, in our study, neither the R factor nor the N factor caused statistically significant differences in prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Thoracic cage reconstruction maintains anatomical and structural stability, protects vital organs, and helps sustain the respiratory mechanism. The procedure is required in 40–60% of individuals who have undergone thoracotomy (1,9,11). Reconstruction is required for individuals with ≥3 resected ribs and defects that are ≥5 cm in diameter or even for patients with smaller defects and cases of suspected thoracic cage instability (911,13,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations